INTERACTIVE GAMIFIED ACTIVITY AS AN AID TO AUTHORING STORIES FOR STUDENTS WITH AUTISM SPECTRUM DISORDER. - Magro, Ana Carolina (2024)
This research aims to understand how gamification, as a teaching strategy, can contribute to the learning of students with Autism Spectrum Disorder (ASD). To this end, an intervention research with a qualitative approach was carried out, organized in stages: prior survey of the particularities, profile and hyperfocus of a student with ASD, planning of the interactive gamified activity, execution and evaluation of the proposal. The research participant was an autistic student in the fourth year of elementary school at a public school in northern Paran & aacute;. The institution participates in the Pedagogical Residency Program. Data were collected through participant observation and student productions during interventions. The results of the investigation showed that gamification can contribute to the learning of autistic students as it is planned with intentionality considering the student's specificities, as well as playfulness and interactivity. It was also possible to verify that the use of the digital artifact and instant feedback contributed to student engagement in carrying out the gamified activity, as there was interest and active participation in writing.